2014
DOI: 10.1371/journal.pone.0089805
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Lead Isotopic Abundances in Sprague-Dawley Rat Tissues: Possible Reason of Formation

Abstract: It has been reported in previous research that the lead isotopic composition of blood, urine and feces samples statistically differed from the given lead sources in Sprague-Dawley (SD) rats. However, the reason for this phenomenon is still unclear. An animal experiment was performed to investigate the lead isotope fractionation in diverse biological samples (i.e., lungs, liver, kidneys, bone) and to explore the possible reasons. SD rats were intratracheally instilled with lead acetate at the concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…However, two studies on rats treated with Pb acetate purport to observe Pb isotopic fractionation because of exchange of Pb between different media. These results have been published by the same authors in 2012 by Wu et al [ 40 ] and in 2014 by Liu et al [ 41 ]. The 2012 studies provided results for blood, urine, and feces and, in addition to these, the 2014 paper gave results for kidneys, liver, lungs and bone.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…However, two studies on rats treated with Pb acetate purport to observe Pb isotopic fractionation because of exchange of Pb between different media. These results have been published by the same authors in 2012 by Wu et al [ 40 ] and in 2014 by Liu et al [ 41 ]. The 2012 studies provided results for blood, urine, and feces and, in addition to these, the 2014 paper gave results for kidneys, liver, lungs and bone.…”
Section: Resultssupporting
confidence: 74%
“… It is also unrealistic to quote Pb isotopic data to 5 decimal places, especially from Q-ICP-MS analyses, although the incredible agreement for blood and urine data from both studies shown in Figure 11 would permit such claims. It is also noteworthy that in the Wu et al [ 40 ] paper the isotopic data are given as ratios but in the Liu et al [ 41 ] the data are presented as % abundances of each isotope, although they do claim, to the contrary, that the % abundances are a better indicator of fractionation. There was no indication if the blood, urine and feces in Liu et al [ 41 ] were the same data from the Wu et al [ 40 ] paper although, as shown in Figure 10 , the almost identical data for blood and urine from both studies and off-set of the urine data would perhaps indicate this.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Cu and Zn isotopic fractionation are very promising for the early diagnosis of different types of cancer (9,12) and neurodegenerative diseases (8,13), whereas Fe and Ca isotopic fractionation measurements have shown their ability to monitor Fe absorption efficiency (3) and bone mineral balance (7), respectively. Concerning high-mass elements, only a few in vivo studies have been reported, within the framework of toxicity investigations and identification of contamination sources, that seem to suggest that isotopic fractionation occurs during metabolic processes for elements such as Pb and Hg (14)(15)(16). However, very little knowledge is available on the processes occurring at the molecular or cellular level that lead to the isotopic fractionation observed during metal transport in living organisms.…”
mentioning
confidence: 99%
“…Isotopic signature in 207 Pb/ 206 Pb is theoretically preserved during trophic transfer as it has been proved for phyton to nekton transfer (GĂ©linas and Schmit, 1997). But biological lead isotopes fractionation was recently observed on rat model (Liu et al, 2014;Wu et al, 2012). After exposure by inhalation to lead acetate, rat's feces 207 Pb/ 206 Pb signature showed significant differences with 207 Pb/ 206 Pb signature of test substance at high-dose exposure even if no differences were observed at neither low nor medium exposure (Wu et al, 2012).…”
Section: Pb Isotopic Compositions Differences Between Casts/earthwormmentioning
confidence: 96%